Supplementation of Antioxidant Liang Tea Extracts on Goat Milk Cream Cheese - Zahrah, Syarifah; Dewi, Yohana Sutiknyawati Kusuma; Hartanti, Lucky (Department of Agro-industrial Technology, University of Brawijaya, 2023)
AbstractCream cheese is a soft cheese that does not go through a ripening process and is widely used in various kinds of food preparations. Goat's milk is an alternative milk for cream cheese production. The addition of antioxidant extract from liang tea potentially produces functional cream cheese. This research aimed to obtain the concentration of added antioxidant liang tea extract in the formulation that produces the best characteristics of goat's milk cream cheese. This research used a Randomized Block Design method with one factor: the concentration of liang tea extract as an antioxidant. The treatment consisted of 5 levels of liang tea concentrations, 0%, 1.5%, 2%, 2.5%, and 3%, with five repetitions. The research showed that adding various concentrations of liang tea antioxidant extract produced a water content of 61.06%-62.09% and a fat content of 12.68%-14.46%. The resulting color characteristics with the L* value range from 60.83-76.43 (decreasing brightness), the* value range from -6.69-6.71 (reddish), and the b* value range from 4.47-23 .88 (yellowish). Antioxidant activity is expressed by percent inhibition of 1,1-diphenyl-2-picrylhydrazil (DPPH), ranging from 36.00%-79.56%. The antioxidant activity of goat's milk cream cheese increases if the addition of liang tea extract is high. Based on the effectiveness index, the best goat's milk cream cheese is produced by adding a 3% concentration of liang tea. The cream cheese has a water content of 62.19%, a fat content of 14.46%, color (L* = 60.83, a* = 6.71, b* = 23.88), and antioxidant activity of 79.56%.Keywords: antioxidant, cream cheese, goat milk, liang tea AbstrakCream cheese merupakan salah satu jenis keju lunak yang tidak melalui proses pematangan dan banyak diaplikasikan pada berbagai macam olahan pangan. Susu kambing menjadi alternatif susu untuk membuat cream cheese. Penambahan ekstrak antioksidan dari liang teh berpotensi untuk membuat cream cheese fungsional. Tujuan penelitian ini untuk memperoleh konsentrasi penambahan ekstrak antioksidan liang teh dalam formulasi yang menghasilkan karakteristik cream cheese susu kambing terbaik. Penelitian ini menggunakan Rancangan Acak Kelompok (RAK) dengan satu faktor, yaitu konsentrasi ekstrak liang teh sebagai antioksidan. Perlakuan yang dilakukan terdiri dari 5 taraf, yaitu 0%, 1,5%, 2%, 2,5% dan 3% dengan 5 kali ulangan. Hasil penelitian menunjukkan penambahan berbagai konsentrasi ekstrak antioksidan liang teh menghasilkan kadar air pada rentang 61,06%-62,09% dan kadar lemak pada rentang 12,68%-14,46%. Karakteristik warna yang dihasilkan dengan rentang nilai L* adalah 60,83-76,43 (kecerahan menurun), nilai a* pada rentang -6,69-6,71 (kemerahan), dan nilai b* pada rentang 4,47-23,88 (kekuningan). Aktivitas antioksidan dinyatakan dengan persen penghambatan 1,1-diphenyl-2-picrylhydrazil (DPPH) pada rentang 36,00%-79,56%. Aktivitas antioksidan cream cheese susu kambing semakin meningkat jika penambahan ekstrak liang teh semakin tinggi. Cream cheese susu kambing terbaik berdasarkan indeks efektivitas dihasilkan dengan penambahan konsentrasi liang teh 3%. Cream cheese tersebut mempunyai kadar air 62,19%, kadar lemak 14,46%, warna (L* = 60,83, a* = 6,71, b* = 23,88), dan aktivitas antioksidan 79,56%.Kata kunci: antioksidan, cream cheese, liang teh, susu kambing